Efficacy of Anesthetics for Reducing Stress in Fish During Aquaculture Practices - A Review - Husen, Md. Akbal; Sharma, Subodh (Kathmandu University Journal of Science, Engineering and Technology, 2014)
Intensification of aquaculture practices has increased the stress level in fish. Transportation, handling, sorting by size, weighing, increased farming density, confinement level, and degradation of water quality are stressors in aquaculture practices which exhibit physiological stress responses in fish. These stressors bring changes in plasma cortisol, glucose, lactase, plasma chloride, sodium, and lymphocyte concentrations in fish. Fish stress and mortality can cause significant losses of resources and productivity in both capture and culture systems. Use of anesthetics with optimum concentration could mitigate the stress and its related harm in fish, by increasing fish welfare, production, and profitability. This review has summarized the aquaculture stress, its related consequences to fish, and the efficacy of anesthetics to reduce these factors.